A Comparison of Mentoring and Coaching: What's the Difference?. Issue 7 (22nd September 2021) - Viera, Carlos Antonio
Abstract: The work of educators in urban high schools may at times seem rather daunting. Teachers serving in these settings are often in search of intervention strategies that can assist in their efforts to support students in achieving improved outcomes. Mentoring and coaching are two powerful interventions that organizations can implement when attempting to improve their outcomes in human performance. The focus of either of these two personal development interventions is on enhancing individuals through organizational opportunities and self‐initiative. However, many times the specific aspects of these two different approaches may be confused and even be referred to interchangeably. A comparison of the fundamental differences between mentoring and coaching will be described in this article. An analysis of the pros and cons of using formal mentoring and coaching programs, as viable performance improvement interventions within an educational organization, will also be presented. Additionally, a brief research‐based plan to develop, implement, and evaluate coaching for secondary Career and Technical Education teachers working in high school settings will also be shared. Specific challenges and barriers to the immediate and long‐term success of the coaching intervention and effective ways to overcome them will also be examined.